ANATOMICAL MORPHO INDEX PROFILE OF TILAPIA (Oreochromis niloticus) CULTIVATED IN THE MINA PADI POND SYSTEM - widianti, lia; Petrus Hary Tjahja, Soedibya; Sri, Marnani (Journal Of Artha Biological Engineering, 2023)
The morphological-anatomical index profile is a value of changes in morphology (outer shape) and anatomy (internal organs) as a basis for calculating fish growth. Fish Growth in terms of morphology includes length and weight, while in terms of anatomy can be seen from changes in gonad, liver, and visceral weight. The purpose of this study was to determine the value of the morpho-anatomical index of Nila Fish GIFT (Oreochromis niloticus) cultured in the POKDAKAN Mina Mandiri pond. This research was conducted in the Mina Mandiri Fish Cultivation Group (POKDAKAN) pond, Panembangan Village, Banyumas from September 23, 2021 – November 28, 2021. The method used in this study was a survey method where the data was processed and analyzed descriptively and compared with the literature related. The results of the morpho-anatomical index of Nila Fish GIFT included a hepatosomatic index (HI) of 0.31%, a viscerasomatic index (VI) of 14.09% and a gonadosomatic index (GI) of 2.61%. The fish condition factor value was 1.05557 and the length-weight relationship was 2.6, which is negative allometric